2011
DOI: 10.1563/aaid-joi-d-09-00098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Ozonated Plant Oils on the Quality of Osseointegration of Dental Implants Under the Influence of Cyclosporin A: An In Vivo Study

Abstract: Immunosuppressive agents have been recognized as factors that induce changes and modifications in bone metabolism. The purpose of this study was to evaluate the effect of ozonated plant extracts (herein termed ozonated oil) under the influence of Cyclosporin A (CsA) on osseointegration. A total of 20 dental implants were placed in 20 rabbit tibiae assigned to Group A or B. CsA was injected at an immunosuppressive dose in Groups A and B as a single-dose treatment. At the day of surgery, Group A received a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…CsA administration does not prevent bone formation and mineralization, but the osteoid maturation and mineralization occur more slowly and a lesser extent. These data close resemble observations made by previous studies (Duarte et al, ; El Hadary et al, ; Sakakura et al, ) that showed impairment of bone healing in animals under CsA therapy started before the implant placement. These findings confirmed the hypothesis that already healed bone around titanium implants might be affected by CsA administration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CsA administration does not prevent bone formation and mineralization, but the osteoid maturation and mineralization occur more slowly and a lesser extent. These data close resemble observations made by previous studies (Duarte et al, ; El Hadary et al, ; Sakakura et al, ) that showed impairment of bone healing in animals under CsA therapy started before the implant placement. These findings confirmed the hypothesis that already healed bone around titanium implants might be affected by CsA administration.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we and others have examined the effects of CsA on bone healing around dental implants (Duarte et al, ; El Hadary, Yassin, Mekhemer, Holmes, & Grootveld, ; Sakakura, Marcantonio, Wenzel, & Scaf, ; Sakakura, Margonar, Sartori, Morais, & Marcantonio, ; Sakakura et al, ). These studies demonstrated that the short or long‐term CsA administration previous to implant placement lead to decreased bone‐to‐implant contact, decreased bone area around the implant threads (BAFO), and poor quality of the bone resulting in lowest torque values for implant removal (Duarte et al, ; El Hadary et al, ; Sakakura et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the various beneficial effects of ozone therapy could be applied in both dental and orthopedic implantology. Modern strategies to prevent implant-associated infections are geared towards treatments and technologies capable of preventing/resisting infections while promoting repair and osseous integration [21][22][23][24].The promotion of peri-implant bone-healing of endosseous implants by an ozonized oil has been experimentally studied in immunosuppressed rabbits [25]. A better osseointegration process in endosseous implants treated with photobiomodulation and ozone therapy has been described [26].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts cultured on ozone-ultraviolet-treated surfaces displayed a significantly higher expression of osteoblast markers, like bone morphogenetic protein 2, and osteocalcin [30]. Ozonized oils and other ozone treatments exhibited the capability to promote the bone integration of dental and orthopedic implants while expressing antimicrobial and even immunomodulatory effects [25,26,31]. However, the fungicidal potential of ozone therapy is still poorly explored.…”
Section: Introductionmentioning
confidence: 99%